Enhancing Early Literacy Through Collaborative Digital Educational Games: A Classroom Action Research with Kindergarten Children Exhibiting ADHD Symptoms - Asmawati, Septi; Mahabbati, Aini (Journal of Innovation and Research in Primary Education, 2025)
Early literacy development presents significant challenges for kindergarten children exhibiting Attention Deficit Hyperactivity Disorder (ADHD) symptoms, who often struggle with concentration and traditional instructional methods. This study investigated the effectiveness of collaborative digital educational games in enhancing early literacy capabilities among children with ADHD symptoms. A classroom action research design following the Kemmis and McTaggart model was implemented over six months with a 5-6 year old male kindergarten student exhibiting ADHD symptoms. The intervention utilized the "Learn ABC" digital educational game within a collaborative learning framework across two cycles. Data collection included oral literacy assessments using a four-point scoring system and structured classroom observations. The intervention involved systematic group formation, collaborative gameplay, and peer presentations, with modifications between cycles based on reflective analysis. Substantial improvements were observed throughout the intervention period. The participant's performance increased from 26.67% at baseline to 88.87% upon completion, representing a 62.2 percentage point improvement that exceeded the established 76% success criterion. Cycle I showed progressive gains from 44.44% to 55.55%, while Cycle II demonstrated accelerated improvement from 66.67% to 88.87%. Qualitative observations revealed enhanced attention span, increased collaborative participation, improved confidence in letter identification, and sustained engagement during gaming activities. The findings demonstrate that collaborative digital educational games can effectively address attention and literacy challenges in children with ADHD symptoms. The intervention's success supports the integration of technology-enhanced collaborative learning approaches in inclusive early childhood education settings. The systematic implementation framework provides a replicable model for educators, though larger-scale studies are needed to establish broader generalizability.